Automating Salesforce Marketing Cloud : reap all the benefits of the SFMC platform and increase your productivity with the help of real-world examples /: reap all the benefits of the SFMC platform and increase your productivity with the help of real-world examples. (2022) - Gifford, Greg; Hanshaw, Jason
No abstract available